The Effect of Audit Fee and Audit Tenure on Audit Quality of Public Accounting Firms in Makassar with Auditor Independence as a Mediating Variable - Gaffar, Gaffar; Gaffar, Muhammad Ichsan; Ibrahim, Melinda (Universitas Pendidikan Indonesia, 2024)
This study aims at finding the effect performed by audit fees and audit tenures on audit quality mediated by auditor independence. This study applies a quantitative research method. The population in this study covers seven public accounting firms covering 61 auditors willing to fill out the questionnaires. The analytical technique used in this study is path analysis. The results of this study indicate that audit fee has a negative and significant effect on audit quality and auditor independence. The audit tenure positively and significantly affects audit quality and audit independence. Auditor independence mediates the audit fees on audit quality. In addition, auditor independence mediates audit tenure on audit quality.